Feeding and reproductive patterns of Astyanax intermedius in a headwater stream of Atlantic Rainforest - Souza, Ursulla P.; Ferreira, Fabio C.; Carmo, Michele A. F.; Braga, Francisco M. S. [UNESP] (Acad Brasileira De Ciencias, 2015)
In this paper, we determined diet composition, reproductive periodicity and fecundity of Astyanax intermedius in a headwater stream of a State Park of an Atlantic rainforest. We also evaluated the influence of rainfall, water temperature and fish size on niche width and niche overlap. Sampling was conducted monthly throughout one year in the Ribeirao Grande stream, southeastern Brazil. Diet consisted of 31 food items with equal contribution of allochthonous and autochthonous items. Females were larger than males, and the mean sizes at first maturation were 4.44 cm and 3.92 cm, respectively. Based on 212 pairs of mature ovaries, the number of oocytes per female ranged from 538 to 6,727 (mean = 2,688.7). Niche width and niche overlap were not related to rainfall nor water temperature and only niche width increased with fish size, suggesting that as fish grow, more items are included in diet. Our results suggested that A. intermedius fit as a typical opportunistic strategist which may explain the prevalence of this species in several isolated headwater basins of vegetated Atlantic forested streams where food resources are abundant and distributed throughout the year.
Keywords: Characidae fishes; niche overlap; niche width; spawning type